The Analysis of Human Feelings: A Practical Suggestion for a Robustness Test. (2nd July 2021) - Bloem, Jeffrey R.; Oswald, Andrew J.
Abstract : Governments, multinational companies, and researchers today collect unprecedented amounts of data on human feelings. These data provide information on citizens' happiness, levels of customer satisfaction, employees' satisfaction, mental stress, societal trust, and other important variables. Yet a key scientific difficulty tends to be downplayed, or even ignored, by many users of such information. Human feelings are not measured in objective cardinal units. This article aims to address some of the ensuing empirical challenges. It suggests an analytical way to approach the scientific complications of ordinal data. The article describes a dichotomous‐around‐the‐median (DAM) test, which, crucially, uses information only on direction within an ordering and deliberately discards the potentially unreliable statistical information in ordered data. Applying the proposed DAM approach, this article shows that it is possible to check and replicate some of the key conclusions of previous research—including earlier work on the effects upon human well‐being of higher income.